Poezia senzationalului și sentimentul tragicului în romanul Îngerul a strigat - Dragoș M. Vicol (Revista de Istorie și Teorie Literară)
Fănuş Neagu’s prose has a special architecture, making use of a great range of figures of speech, with the intention of enchanting the reader and, simultaneously, of describing the wondrous landscape of Bărăgan and the Danube pools. His word choice is rich and expressive, very much resembling that of Sadoveanu’s. In the same time, the vernacular realism is combined with an ancestral wisdom and this is the secret of an incomparable art of story-telling.